From sequencing to hardware acceleration of DNA alignment software: A integral review - Pacheco Bautista, D.; González Pérez, M.; Algredo Badillo, I. (Revista Mexicana de Ingenieria Biomedica, 2015)
In recent years, impressive progress has occurred in the machines of massively parallel sequencing, also called of next-generation sequencing (NGS), for example, recent machines like Illumina HiSeq are capable of generating millions of reads in a single run. However, these technologies are limited to sequence only small fragments of genetic material (35 to 1100 nucleotides), so that for complete-genome sequencing, it is necessary to divide the chain, to sequence the fragments, and,subsequently, to assemble the obtained short readings. In this paper, the recent NGS sequencing technologies are reviewed and compared, analyzing the problem of sequence assembly, and formally establishing the problem of alignment. Also, it is examined the main alignment programs and the algorithms that support them. Finally, after concluding that sequencing technologies have speed that exceeds 10 times to the speed of the alignment programs, the hardware acceleration is reviewed as an alternative to accelerate these programs. This work, which is a comprehensive analysis and review, aims to contribute to the development of the research in the area of bioinformatics in the country.